2003
DOI: 10.1542/peds.111.6.e661
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Hemolytic Transfusion Reaction/Hyperhemolysis Syndrome in Children With Sickle Cell Disease

Abstract: DHTR/H syndrome occurs in pediatric SCD patients, typically 1 week posttransfusion, and presents with back, leg, or abdominal pain; fever; and hemoglobinuria that may mimic pain crisis. Hb is often lower than it was at the time of original transfusion, suggesting the hemolysis of the patient's own RBCs in addition to hemolysis of the transfused RBCs; a negative DAT and reticulocytopenia are often present. Severe complications including acute chest syndrome, congestive heart failure, pancreatitis, and acute ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
192
1
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(208 citation statements)
references
References 14 publications
7
192
1
6
Order By: Relevance
“…Further transfusions are avoided as best as possible. Similar observations were documented by Talano J-AM and colleagues in their report of hyperhaemolysis in SCD children [3].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Further transfusions are avoided as best as possible. Similar observations were documented by Talano J-AM and colleagues in their report of hyperhaemolysis in SCD children [3].…”
Section: Discussionsupporting
confidence: 87%
“…SCD usually requires red blood cell transfusions to manage complications including anaemia, acute chest syndrome, stroke and splenic sequestration. Alloimmunization is a serious complication after exposure to donor or foreign red cells and incidence is reported as high as 5 to 36 % in SCD patients [3,4]. Clinical manifestations of delayed haemolytic transfusion reactions (DHTR) can be different from those described in other patients.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] DHTR has been reported to occur in 4-11% of SCD patients given blood transfusions. 6,[10][11][12] DHTRs occur from a few days to two weeks after a blood transfusion and manifest as clinical features of acute hemolysis (hemoglobinuria, jaundice, and pallor) combined with symptoms suggesting severe vaso-occlusive crisis (pain, fever, and sometimes acute chest syndrome). The destruction of both the donor's and the recipient's RBCs leads to an abrupt drop in the hemoglobin level, to a value lower than the pre-transfusion value.…”
Section: Introductionmentioning
confidence: 99%
“…Corticosteroid and/or intravenous immunoglobulin (IVIg) therapy has been reported to ensure recovery from DHTR. [5][6][7][8][9]13,14 More recently, two studies reported the use of rituximab for preventing DHTR. 13,15 The pathophysiology of this syndrome remains unclear, especially when there is no detectable antibody.…”
Section: Introductionmentioning
confidence: 99%
“…Delayed hemolytic transfusion reactions usually occur between one and four weeks post-transfusion (Beers et al, 2006) and represent approximately 11% of all complications of RBC transfusions (Talano et al, 2003). The mechanism is due to alloantibodies formed against One-third of delayed hemolytic transfusion reactions (DHTR) are mediated by the Kidd antibody.…”
Section: Discussionmentioning
confidence: 99%